Optimisme Dan Dukungan Sosial Teman Sebaya : Perannya Terhadap Resiliensi Akademik Mahasiswa Tingkat Akhir - Sandayanti, Vira; Binangkit, Gina Gevanty (Universitas Pahlawan Tuanku Tambusai, 2025)
Students are usually in early adulthood, the difficult situations faced by students will increase in line with the increase in semester level, especially students who are working on their thesis. The ease experienced when working on a thesis requires students to have good academic resilience and be supported by internal factors such as optimism or confidence in their abilities and external factors, namely social support from their peers. The purpose of this study was to determine the relationship between optimism and peer social support with the resilience of academic students who are working on their thesis. The subjects of this study were 7-8 semester students at Malahayati University who were working on their thesis. The number of samples was 186 students, consisting of 101 famale and 85 male. The research data were taken using a scale of academic resilience, optimism, and peer social support. Data analysis used multiple linear regression tests. The results showed that there was a relationship between optimism and peer social support together with academic resilience of 69.7%. Keyword: Academic Resilience, Optimism, Peer Social Support, Final Year Student